EXAMINING PROJECT-BASED LEARNING IN HIGHER EDUCATION: STUDENT OUTCOMES AND EVALUATION MEASURES (International Journal of Food and Nutritional Sciences, 2022)
It is believed that project-based learning (PjBL) is a potential strategy for enhancing student learning in higher education. Examining empirical research on projectbased learning, student outcomes have been the main focus of the review. Most often, questionnaires, interviews, observation, and self-reflection journals were used to examine affective outcomes, or opinions on the experience and advantages of PjBL. Questionnaires, rubrics, exams, interviews, observation, self-reflection journals, artifacts, and log data were used to measure behavioral outcomes (skills and engagement) and cognitive outcomes (knowledge and cognitive strategies). Rubrics were used to evaluate the performance of the item. Further studies should look into the end products and learning processes of pupils. Enhancements should also be made to data analysis and measurement tools.